Financial Stability Reports in Latin America and the Caribbean - Lim, Cheng; Klemm, Alexander; Ogawa, Sumiko; Pani, Marco (Washington, D.C. : International Monetary Fund, 2017)
Many countries in Latin America and the Caribbean now publish financial stability reports. This study reviews their latest issues to assess their content, quality, and transparency. While some reports provide a strong analysis of risks and vulnerabilities, there are significant cross-country differences, and many reports could be improved by adopting a more comprehensive, forward-looking, and thematic assessment of financial stability. A well thought out communication strategy, including a regular and predictable publication schedule and an easily accessible website, is also important to enhance the impact of the reports. Data gaps, particularly at the disaggregated level, are material and need to be urgently addressed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet